r 2002
DOI: 10.20955/r.84.65-94
|View full text |Cite
|
Sign up to set email alerts
|

Market Anticipations of Monetary Policy Actions

Abstract: There is some well-documented persistence in deviations of the funds rate from the funds rate target. For example, see Taylor (2001). 8 This and subsequent analyses ignore the possibility of a small premium in the futures market, documented by Robertson and Thornton (1997), because any such premium is so small that its existence would have a negligible impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 23 publications
5
129
0
2
Order By: Relevance
“…The estimates from previous studies that are reported in Table 1 are for part of the Greenspan chairmanship. The estimates in Table 2 or 3 for the part of the Greenspan chairmanship for which we have data are on the high end of the studies in Table 1, close to those of Poole et al (2002), line 11, for the earlier part of Greenspan tenure. 12 Effects of anticipated policy actions: when the 1-year interest rate is the dependent variable, a number of the coefficients on the anticipated component of the federal funds rate are significant; for the 10-year rate these coefficients are small and some are insignificant.…”
Section: Estimation Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The estimates from previous studies that are reported in Table 1 are for part of the Greenspan chairmanship. The estimates in Table 2 or 3 for the part of the Greenspan chairmanship for which we have data are on the high end of the studies in Table 1, close to those of Poole et al (2002), line 11, for the earlier part of Greenspan tenure. 12 Effects of anticipated policy actions: when the 1-year interest rate is the dependent variable, a number of the coefficients on the anticipated component of the federal funds rate are significant; for the 10-year rate these coefficients are small and some are insignificant.…”
Section: Estimation Resultssupporting
confidence: 64%
“…Gurkaynak et al (2006) find that monetary surprises do not have a significant effect on the 10-year interest rate for the sample period 1998-2005, in contrast to the finding of Gurkaynak et al (2005a), using the same methodology for the sample period 1990-2002. The estimates from Poole et al (2002), line 10 of Table 1, show no significant effect of monetary surprises on interest rates with maturities beyond 1 year for the 1994-2001 period. Swiston finds no effect for monetary surprises in an update of Kuttner (2001) for the years 2000-2006.…”
Section: Interpretation and Conclusionmentioning
confidence: 89%
“…Yields are expressed in basis points at annual rates and the three returns are expressed in daily rates in percentages by computing the di¤erences of the logarithms of the index with the result multiplied by 100. 9 All variables are demeaned. 10 Table 1 shows the standard deviations for yield changes, equity and the exchange rate returns for the three regimes: US event days, Australian event days, and nonevent days.…”
Section: Variablesmentioning
confidence: 99%
“…To test the whether the market was aware that the Fed was targeting the funds rate before the late 1980s, Equation 1 was estimated partitioning target changes into those that occurred before 1991 and after 1990-the date identified by Poole, Rasche and Thornton (2002). The results, presented in Table 5, show that the response of the T-bill rate was small and only marginally significant before 1991; however, it was more than three times larger and highly significant after 1990.…”
Section: When Did the Market Know That The Fed Was Targeting The Fundmentioning
confidence: 99%
“…Hence, consistent with the conventional open market view of monetary policy, the Fed appears to exert considerable control over the federal funds rate. By mid-May, however, the funds rate was trading below the target and the market began to revise its expectations for the funds rate for June and beyond (see Poole, Rasche and Thornton, 2002, the appendix, for details).…”
mentioning
confidence: 99%